2013
DOI: 10.1021/es303264c
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Brominated Epoxy Resins by Dimethyl Sulfoxide To Separate Waste Printed Circuit Boards

Abstract: Improved methods are required for the recycling of waste printed circuit boards (WPCBs). In this study, WPCBs (1-1.5 cm(2)) were separated into their components using dimethyl sulfoxide (DMSO) at 60 °C for 45 min and a metallographic microscope was used to verify their delamination. An increased incubation time of 210 min yielded a complete separation of WPCBs into their components, and copper foils and glass fibers were obtained. The separation time decreased with increasing temperature. When the WPCB size wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…The TGA-DTG of recovered residue and untreated substrate resin (Fig. 8) shows similar thermal degradation profile having significant weight loss in 290e350 C range and maximum instantaneous weight loss at 330 C. The results obtained also agree with the results reported in other literature (resin decomposition range 260e400 C) (Lin and Chiang, 2014;Zhu et al, 2013). The FT-IR spectra of residue have shown vibrations corresponding to para distributed aromatic compound and CeH, CeC, C]C stretching of aromatic ring.…”
Section: Recycling Of Solvent and Analysis Of Residuesupporting
confidence: 87%
See 1 more Smart Citation
“…The TGA-DTG of recovered residue and untreated substrate resin (Fig. 8) shows similar thermal degradation profile having significant weight loss in 290e350 C range and maximum instantaneous weight loss at 330 C. The results obtained also agree with the results reported in other literature (resin decomposition range 260e400 C) (Lin and Chiang, 2014;Zhu et al, 2013). The FT-IR spectra of residue have shown vibrations corresponding to para distributed aromatic compound and CeH, CeC, C]C stretching of aromatic ring.…”
Section: Recycling Of Solvent and Analysis Of Residuesupporting
confidence: 87%
“…Liberation of metals by solvent eliminates the need of down-sizing of WPCBs to fine size and metal-nonmetal separation and thus, it offers more economical processing, relatively. Previous studies also expressed that solvent DMF is better than other reported solvents viz.-dimethylsulfoxide (Zhu et al, 2013) and N, N-dimethyl pyrrolidone (Wath et al, 2015). DMF offers lower energy consumption, better mass transfer, and lower evaporation rates, comparatively.…”
Section: Introductionmentioning
confidence: 95%
“…Meanwhile, hydrogen in the methyl group in DMSO may form hydrogen bonds with bromine and oxygen in BER (Fig.10) [32].…”
Section: Chemical and Structural Propertiesmentioning
confidence: 99%
“…Fig. 10C shows that the methyl group of DMSO gives its hydrogen to form hydrogen bonds with oxygen and bromine in BER [32].…”
Section: Chemical and Structural Propertiesmentioning
confidence: 99%
“…Leaching is the most common disposal procedure in hydrometallurgy, and the common leaching systems for metal recovery include sulfuric acid [15], nitric acid [16], hydrochloric acid [17], ammonia [18]. However, common inorganic solvents will result in amounts of waste acid or alkali solutions, which is hard to treat.Recently the study about ionic liquid (IL) provides a new possibility for the pollution-free hydrometallurgical process [19,20]. Ionic liquids, also called room temperature ionic liquids (RTILs), are known as a perspective green solvent because of special properties, such as negligible volatility, low toxicity, thermal stability, high conductivity and wide electrochemical window.…”
mentioning
confidence: 99%